2017
DOI: 10.1007/s13224-017-0984-5
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Red Cell Alloantibodies in Pregnant Females of Navsari District: An Experience that Favours Inclusion of Screening for Irregular Erythrocyte Antibody in Routine Antenatal Testing Profile

Abstract: Red cell alloimmunisation is not uncommonly observed in pregnant females; the information gained can help the obstetrician to identify high-risk cases to timely start antenatal and post-natal treatment. Obstetricians should request screening for irregular red cell antibody desirably in all pregnant females; however, if limiting factors are there, it should be done at least in select group of pregnant females having bad obstetric history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…The distribution of maternal alloimmunization varies in different populations in different countries. The alloimmunization rate in this study was 9.8%, with that among the D − participants being 24.4%, which is much higher than reported by Das et al 4 (2.27%), Sahoo et al 12 (3.6%), and Kahar 13 (1.02%) in studies conducted in India and Europe, where the prevalence was in the range of 0.5-2.57%. The higher rate of alloimmunization in this study could be due to the variations in the population ethnicity.…”
Section: Discussioncontrasting
confidence: 66%
“…The distribution of maternal alloimmunization varies in different populations in different countries. The alloimmunization rate in this study was 9.8%, with that among the D − participants being 24.4%, which is much higher than reported by Das et al 4 (2.27%), Sahoo et al 12 (3.6%), and Kahar 13 (1.02%) in studies conducted in India and Europe, where the prevalence was in the range of 0.5-2.57%. The higher rate of alloimmunization in this study could be due to the variations in the population ethnicity.…”
Section: Discussioncontrasting
confidence: 66%
“…The largest number of cases was associated with anti-D with a frequency of 86.4%, as evidenced by the eluate test, which is justified by the fact that the D antigen is highly immunogenic, and it is the most associated to triggering the disease 3 . Scientifical studies confirm that anti-D is still the most frequent and is the main cause of HDN, being responsible for 80% to 90% of cases 5,6 .…”
Section: Discussionmentioning
confidence: 98%
“…Findings from this study showed that the prevalence of Rh alloimmunization was 17.1%. Results from this study were relatively higher than those from studies conducted in Jimma (14.3%) ( 31 ), western Uganda (3.6%), South Western Uganda (3.9%), and Western Uganda (5.7%) ( 22 , 32 – 34 ), respectively; a systematic review conducted in sub-Saharan Africa (6.7%) ( 32 ), India (4.2%), (6.9%), (10.4%) ( 22 , 33 , 34 ), respectively; and USA (0.74%) ( 35 ). The possible justifications include the use of advanced diagnosis and early booking of ANC, sample size, and socioeconomic characteristics of study participants.…”
Section: Discussionmentioning
confidence: 99%